Answer:
C. 1.11
Step-by-step explanation:
Ball: f(x) = 24 − 16x^2
Balloon: g(x) = 4x
4x = 24 - 16x^2
16x^2 + 4x - 24 = 0
4x^2 + x - 6 = 0
[tex] x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a} [/tex]
[tex] x = \dfrac{-1 \pm \sqrt{1^2 - 4(4)(-6)}}{2(4)} [/tex]
[tex] x = \dfrac{-1 \pm \sqrt{1 + 96}}{8} [/tex]
[tex] x = \dfrac{-1 \pm \sqrt{97}}{8} [/tex]
[tex] x = \dfrac{-1 + \sqrt{97}}{8} [/tex] or [tex] x = \dfrac{-1 - \sqrt{97}}{8} [/tex]
We discard the negative solution.
[tex] x = 1.11 [/tex]
Answer: C. 1.11